Web-Based Junior High School Student Attendance System with Face Recognition Feature using the Prototyping Method - Kaesmetan, Yampi R; Rosid, Achmat; Fryonanda, Harfebi (Nusantara Journal of Artificial Intelligence and Information Systems, 2025)
Technology is increasingly developing and innovating rapidly. Among them is the use of technology in various fields, especially in education. Teachers and students at the school still carry out attendance activities manually, namely with a conventional system that requires data recording for each attendance on paper. This system is vulnerable to damage or loss of data because the attendance results there still use paper. The attendance system that utilizes face recognition technology is the system proposed for the formulation of the problem that will be used for the research. The development method of this research uses the Prototyping method which prioritizes speed and time efficiency so that it is very suitable for use considering the current needs for a system that requires speed and accuracy. The framework used in the development of the system is Codeigniter 4. The process of working on the system is system requirements analysis, display design, coding, and testing. The results of the study are to create a website-based attendance application at SMP Daarus Sa'adah by utilizing face recognition technology which is carried out by auto-detecting faces so that it can facilitate users in carrying out attendance activities accurately and quickly.